Interface dependent magnetic moments in Cu/Co,Ni/Cu/Si(001) epitaxial structures - Vaz, C; Lauhoff, G; Bland, J; Langridge, S; Bucknall, D; Penfold, J; Clarke, J; Halder, S; Tanner, B (2007)
The effect of the interface on the magnetic moment of Cu/Co,Ni/Cu/Si(0 0 1) epitaxial structures was studied by polarised neutron reflection (PNR). The structure consists of a specially designed three-step sample (single 60 Å Ni and 10 Å Co films and a 10 Å Co/60 Å Ni bilayer) grown under the same conditions in order to eliminate variations in the magnetic properties that could result from different growth environments. Independent structural characterisation of the samples was also determined from grazing incidence X-ray scattering, therefore increasing the confidence of the PNR fits. High precision PNR measurements performed at room temperature up to a wavevector range of 0.05 Å- 1 yield values of 0.58 ± 0.03 μB and 0.59 ± 0.03 μB per Ni atom for the Ni/Cu(0 0 1) and Co/Ni/Cu(0 0 1) samples, respectively; for the Co layers, the moments per Co atom are 1.63 ± 0.13 μB and 1.68 ± 0.11 μB for the Co/Ni/Cu(0 0 1) and Co/Cu(0 0 1) samples, respectively. Our results show that there are no significant changes in the respective Co and Ni magnetic moments at the Co/Ni interface. © 2007 Elsevier B.V. All rights reserved.